2021
DOI: 10.12669/pjms.37.2.2670
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of Montelukast Sodium in Children with Adenoid Hypertrophy

Abstract: Background & Objectives: Generally, the blockage of upper respiratory tract in children is seen with the hypertrophy of adenoids and tonsils. Normally for patients with adenoid hypertrophy (AH), Adenoidectomy with or without Tonsillectomy is carried out, however it has its own complications like haemorrhage and recurrence of adenoid tissue. Consequently, therapeutic approach has increased extraordinary consideration rather than surgical procedure. The inflammatory process proposed for AH has prompted the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…It mainly benefits from the enhanced inhibitory effect of montelukast sodium on leukotrienes, which reduces the destructive impact of leukotrienes on the immune system, improves immune capacity, and effectively promotes the rehabilitation of children. 30,31 This result is consistent with similar reports at home and abroad. In this study, we also found that the recovery time of related symptoms in the study group was shorter than that in the control group (P < 0.05), and the difference was prominent.…”
Section: Comparison Of Symptom Recovery Between Both Groupssupporting
confidence: 92%
“…It mainly benefits from the enhanced inhibitory effect of montelukast sodium on leukotrienes, which reduces the destructive impact of leukotrienes on the immune system, improves immune capacity, and effectively promotes the rehabilitation of children. 30,31 This result is consistent with similar reports at home and abroad. In this study, we also found that the recovery time of related symptoms in the study group was shorter than that in the control group (P < 0.05), and the difference was prominent.…”
Section: Comparison Of Symptom Recovery Between Both Groupssupporting
confidence: 92%
“…Our study contains seven RCTs 13–19 with 742 included children. Among them, there were 347 males and 395 females.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, seven studies matched our inclusion criteria and were included in the final analysis. [14][15][16][17][18][19][20] The process of our study selection is shown in the PRISMA flow diagram (Figure 1).…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 8 , 9 ] Therefore, non-surgical treatments are often the first choice of parents. Montelukast [ 19 , 20 ] and intranasal corticosteroids are important treatment options for AH. However, montelukast is associated with potential risks, including hyperactivity, sleep disorders, and depression.…”
Section: Discussionmentioning
confidence: 99%